Біблійний вимір роману Паоло Коельо «Алхімік» - Остапенко, Л. М. (My University, 2022)
У статті розглянуто біблійний вимір найвідомішого роману Паоло Коельо «Алхімік». Автор статті віднаходить біблійні образи і мотиви та досліджує їх функціонування у творі. Зміст статті ставить під сумнів традиційне тлумачення «Алхіміка» як книги, написаної для віруючих людей. На противагу поширеним уявленням про твір розвідка доводить, що постмодерна рецепція біблійних образів і мотивів у романі Коельо полягає у спростуванні біблійного наративу. Автор статті вважає, що функціонування біблійних елементів у «Алхіміку» нагадує алхімічну практику апеляції до Святого Письма. У романі «Алхімік» Коельо позбавляє біблійні образи первісної сакральної семантики і наповнює їх профанним змістом. Святий Яків (Сантьяго) відмовляється служити Бо-гові заради мандрів. Ісус відкриває таємницю про земні скарби у пророчому сні Сантьяго. Старозавітний первосвященник Мелхиседек за винагороду вказує герою шлях до земних скарбів. Священні Урім і Тумім стають атрибутами ворожби. Пустеля з сакрального простору спілкування з Творцем перетво-рюється на місце, підкорене людиною, а церква стає кошарою для вівців. Послуговуючись Біблією, Паоло Коельо втілює ідею, яка суперечить біблій-ному віровченню. Євангельська притча про Марфу і Марію, що є епіграфом твору, застосовується письменником як засіб подвійного кодування рома-ну. На перший погляд, письменник не висловлює сумнів щодо теоцентрич-ності світу і визначальної ролі у ньому волі Творця. Однак у романі Коельо підкреслює божественну природу людини не в біблійному сенсі як створену за подобою Творця, а навпаки як здатну скеровувати Божу волю. «Алхімік» геть позбавлений етичних настанов Біблії. Тоді як біблійне віровчення і в юдейській, і в християнській традиціях вбачає призначення людини у досяг-ненні духовної досконалості, у романі пропагується набуття людиною матеріальних благ. Дослідження біблійного виміру роману «Алхімік» демонструє декларування Паоло Коельо антропоцентричної системи цінностей. Автор статті вва-жає, що феномен популярності твору пояснюється великим попитом на ці ідеї у сучасному світі.
The article examines the biblical code of Paolo Coelho’s most famous novel The Alchemist. The author of the article finds biblical images and motifs and also examines their functioning in the work. The content of the article calls into question the traditional interpretation of «The Alchemist» as a book written for religious people. Contrary to popular ideas about the work, the investigation proves that the postmodern reception of biblical images and motifs in Coelho’s novel consists in refuting the biblical narrative. The author of the article believes that the functioning of biblical elements in «The Alchemist» resembles the alchemical practice of appealing to the Holy Scriptures. In the novel «The Alchemist» Coelho strips biblical images of their original sacred semantics and fills them with profane meaning. Saint James (Santiago) refuses to serve God for the sake of wandering. Jesus reveals the secret of earthly treasures in Santiago’s prophetic dream. The Old Testament high priest Melchizedek shows the hero the way to earthly treasures for a reward. The sacred Urim and Thummim become attributes of divination. The desert is transformed from a sacred space of communication with the Creator to a place conquered by man, and the church becomes a sheepfold. Using the Bible, Paolo Coelho embodies an idea that contradicts biblical belief. The Gospel parable about Martha and Mary, which is the epigraph of the work, is used by the writer as a means of double encoding of the novel. At first glance, the writer does not doubt the theocentricity of the world and the determining role of the Creator’s will in it. However, in the novel, Coelho emphasizes the divine nature of man not in the biblical sense as created in the image of the Creator, but on the contrary as capable of directing God’s will. «The Alchemist» is completely devoid of the ethical guidelines of the Bible. While the biblical creed in both the Jewish and Christian traditions sees the purpose of man in achieving spiritual perfection, the novel promotes the acquisition of material goods by man. According to the author of the article, the study of the biblical code in the novel «The Alchemist» demonstrates the declaration of Paolo Coelho’s anthropocentric value system. The author of the article believes that the phenomenon of the popularity of this work is explained by the great demand for these ideas in the modern world.
Keywords: Паоло Коельо; «Алхімік»; біблійний вимір